PERMISSIVE PARENTING AND PEER CONFORMITY WITH JUVENILE DELINQUENCY - Lestari, Sri Kusti Ningsih; Dewi, Salamiah Sari (Research and Development Journal of Education, 2025)
The purpose of this study was to determine and analyze the relationship between permissive parenting and peer conformity with juvenile delinquency in SMP Negeri 5 Medan. The method used is a quantitative research method. The population in this study was 735 students. The sample used in this study was 205 students. The sampling technique used in this study used a purposive sampling technique. There is a significant positive relationship between peer conformity and juvenile delinquency from the coefficient value (Rxy) = 0.534, p = 0.000 < 0.050. The coefficient of determinant (R2) value has a value of 0.286, the conformity of students' peers in the school contributes 28.6% to juvenile delinquency in SMP Negeri 5 Medan. From the results of multiple regression analysis, it is known that there is a relationship between permissive parenting and peer conformity with juvenile delinquency. This is indicated by the coefficient F reg = 46.194 with p < 0.05, and the correlation coefficient R = 0.560 with p < 0.05 and R2 = 0.314; the contribution of permissive parenting and peer conformity in causing juvenile delinquency is 31.4%.